Rojas, E., Paraguay, L. & Quispe A. (2023). Testimonies of sterilized women: rights violations and resilience in rural Peruvian communities. Huancayo: Lliu Yawar, 2023, 197 pp. - Ramos-López, Juan (2024)
The book of Rojas; Paraguay & Quispe (2023), titled "Testimonies of sterilized women: rights violations and resilience in rural Peruvian communities." The main objective of the authors was to understand the situation of women victims of forced sterilizations, from rural communities in the regions of Huancavelica, Ayacucho and Cusco. The methodology used was qualitative, with a gender, human rights, descriptive and ethnographic approach, which was characterized by its participatory and self-reflective approach. The research instruments, for collecting the memories of the stylized women, were the interview, questionnaires and participant observation. The research was carried out during the years from 2020 to 2022.